Report on the economic performance and convergence of the CARICOM Region (for the year ending December 31, 1996) (The Centre St. AugustineTT, 1997)
Looks at the regional economic performance as well as the comparative economic performance of CARICOM and the rest of the world. Focuses on economic and regional performance of CARICOM countries and prospective economic and convergence trends. Makes conclusions.
DC